Identification of key root volatiles signaling preference of tomato over spinach by the Root Knot Nematode Meloidogyne incognita - Murungi, L.K.; Kirwa, H.; Coyne, D.; Teal, P.E.; Beck, J.J.; Torto, B. (American Chemical Society, 2018)
The root knot nematode, Meloidogyne incognita (Kofoid and White) Chitwood, is a serious pest of tomato (Solanum lycopersicum) and spinach (Spinacea oleracea) in sub-Saharan Africa. In East Africa these two crops are economically important and are commonly intercropped by smallholder farmers. The role of host plant volatiles in M. incognita interactions with these two commodities is currently unknown. Here, we investigate the olfactory basis of attraction of tomato and spinach roots by the infective second stage juveniles (J2s) of M. incognita. In olfactometer assays, J2s were attracted to root volatiles from both crops over moist sand (control), but in choice tests using the two host plants, volatiles of tomato roots were more attractive than those released by spinach. Root volatiles sampled by solid phase microextraction (SPME) fiber and analyzed by gas chromatography/mass spectrometry (GC/MS) identified a total of eight components, of which five (2-isopropyl-3-methoxypyrazine, 2-(methoxy)-3-(1-methylpropyl)pyrazine, tridecane, and α- and β-cedrene) occurred in the root-emitted volatiles of both plants, with three (δ-3-carene, sabinene, and methyl salicylate) being specific to tomato root volatiles. In a series of bioassays, methyl salicylate contributed strongly to the attractiveness of tomato, whereas 2-isopropyl-3-methoxypyrazine and tridecane contributed to the attractiveness of spinach. M. incognita J2s were also more attracted to natural spinach root volatiles when methyl salicylate was combined than to spinach volatiles alone, indicating that the presence of methyl salicylate in tomato volatiles strongly contributes to its preference over spinach. Our results indicate that since both tomato and spinach roots are attractive to M. incognita, identifying cultivars of these two plant species that are chemically less attractive can be helpful in the management of root knot nematodes.